Bonjour,
Factoriser les expressions:
A = (2x + 3)(-4x + 1) + (2x + 3)(8 - x)
(2x+3)(-4x+1+8-x)= (2x+3)(-5x+9)= - (2x+3)(5x-9)
B = (4 - 5x)(8x + 1) – (4 - 5x)(7x – 5)
(4-5x)(8x+1-7x+5)= (4-5x)(x+6)= -(5x-4)(x+6)
C = (7 - 2x)(4 + 3x) + (2 - 7x)(3x + 4)
(3x+4)(7-2x+2-7x)= (3x+4)(-9x+9)= -9 (3x+4)(x-1)
D = (9x – 4)(2x + 1) + (9x - 4)2
(9x-4)(2x+1+9x-4)= (9x-4)(11x-3)
E = (2x - 9)(x – 7) + 3(2x - 9)
(2x-9)(x-7+3)= (2x-9)(x-4)
F = 3(7x + 1)(4 - 2x) + (5 - x)(7x + 1)
(7x+1)[ 3(4-2x)+5-x ]= (7x+1)(12-6x+5-x)= (7x+1)(-7x+17)= -(7x+1)(7x-17)